1975
DOI: 10.1111/j.1524-4725.1975.tb00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Ulcers on the Legs With Hyperbaric Oxygen

Abstract: Skin ulcerations present in patients being treated for other conditions with hyperbaric oxygen were noted to heal at an accelerated rate. This observation led to the concept of topical exposure to hyperbaric oxygen as a treatment of intractable cutaneous ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

1978
1978
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 2 publications
(3 reference statements)
0
10
1
Order By: Relevance
“…In 1969, Fisher introduced the topical HBO treatment with a small chamber for an open wound on the lower leg extremity for 2 -3 h twice a day and achieved good results [10,11]. Ravina et al reported a simple, disposable, hyperbaric oxygen device with a polyethylene bag for the treatment of wounds [12].…”
Section: Discussionmentioning
confidence: 99%
“…In 1969, Fisher introduced the topical HBO treatment with a small chamber for an open wound on the lower leg extremity for 2 -3 h twice a day and achieved good results [10,11]. Ravina et al reported a simple, disposable, hyperbaric oxygen device with a polyethylene bag for the treatment of wounds [12].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of observational studies reported successful results with TOT. [21][22][23][24] In a recent observational case series study, Gordillo et al, reported promising results with TOT in patients with non-healing chronic wounds who achieved good wound healing, an observation which was confirmed by a significant increase in VEGF expression on biopsy samples obtained from the edge of the wounds. 25 In a more recent non-randomized controlled study conducted by Blackman et al on 28 patients with diabetic foot ulcers (DFUs), the mean healing duration was shown to be significantly shorter with TOT as compared with standard wound care [56 days in 14 of the 17 (82.4%) patients vs. 93 days in 5 of the 11 patients (45.5%)].…”
Section: Introductionmentioning
confidence: 99%
“…Fisher (3,4) and others (5)(6)(7) have reported marked acceleration of wound healing in patients with leg and foot ulcers of various etiologies (including diabetes mellitus) as a result of treatment with topical hyperbaric oxygen (THO). However, because these studies were retrospective and uncontrolled (3)(4)(5)(6) or the assignment of subjects to oxygen versus control therapy was apparently arbitrary (7), the validity of their conclusions is subject to scientific criticism.…”
mentioning
confidence: 99%